Enemistad aparente: la tensión entre el concepto de graves violaciones de derechos humanos de la Corte Interamericana con el derecho penal - Lengua Parra, Adrián (2020)
From the judgment of the Barrios Altos case vs. Peru, the InterAmerican Court of Human Rights began to develop the concept of «serious violations of rights» and their consequences in the national criminal sphere. Despite being a consolidated standard, nowadays there are still doubts about what acts should be classified under such legal category and if it is correct to limit certain procedural and criminal guarantees in order to achieve their criminalization. This paper explains these controversies in order to propose a legal solution that avoids impunity and ensures the legitimacy of the legal system.